1995
DOI: 10.1159/000239355
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Enhancement of Bactericidal Activity of Phagocytes against <i>Klebsiella pneumoniae </i>Treated with Subminimal Inhibitory Concentrations of Cefodizime

Abstract: The effects of a sub-MIC of cefodizime on the morphology of the capsular structures and on the surface physicochemical properties, such as hydrophobicity and charge, of encapsulated Klebsiella pneumoniae were studied. The enhancement of bactericidal activity of macrophages against bacteria treated with sub-MICs of antibiotics was evaluated as the killing index. Cefodizime treatment gave the highest value of 32. Electron microscope observations revealed that the capsular material layer of cefodizime-treated K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Prior exposure of a subinhibitory aztreonam concentration increased the hydrophobicity and phagocytic killing of P. aeruginosa, while brief exposures to suprainhibitory concentrations had similar effects on other Gram negative bacteria (E. coli, Serratia marcescens, Klebsiella pneumoniae and Salmonella Typhimurium) (55). Subinhibitory cefodizime treatment of K. pneumoniae cells rendered the cells more hydrophobic and more susceptible to phagocytic killing than seen with untreated bacteria (56). Interestingly, bacterial hydrophobicity seems to counteract a lack of opsonization and ensures competent phagocytosis without the presence of complement or immunoglobulins.…”
Section: Discussionmentioning
confidence: 94%
“…Prior exposure of a subinhibitory aztreonam concentration increased the hydrophobicity and phagocytic killing of P. aeruginosa, while brief exposures to suprainhibitory concentrations had similar effects on other Gram negative bacteria (E. coli, Serratia marcescens, Klebsiella pneumoniae and Salmonella Typhimurium) (55). Subinhibitory cefodizime treatment of K. pneumoniae cells rendered the cells more hydrophobic and more susceptible to phagocytic killing than seen with untreated bacteria (56). Interestingly, bacterial hydrophobicity seems to counteract a lack of opsonization and ensures competent phagocytosis without the presence of complement or immunoglobulins.…”
Section: Discussionmentioning
confidence: 94%
“…The PspA molecule has been shown to have anti-complementary properties [84,85,99,100], and an increase of bacterial surface charge has been correlated to a decrease in antibacterial phagocytic activity [101]. The negatively charged PspA could simply repel complement molecules and prevent their interaction with pneumococci, a process necessary for proper function of complement system leading to pneumococcal cell death.…”
Section: Functional Properties Of the N-terminal Module Of Pspamentioning
confidence: 99%
“…Previously, we reported that the treatment of K. pneumoniae with a sub-MIC of cefodizime reduced the thickness of the capsular layer and that associated changes in physicochemical properties of the surface of the bacteria rendered K. pneumoniae more susceptible to phagocytic activity in the ab sence of complement and capsule-specific antibody [8], Other investigators reported that K. pneumoniae and Bacteroides fragilis, which were treated with a sub-MIC antibiotic, showed reduced capsular formation [13,14], Williams [12] reported that K. pneumoniae treated with sub-MIC cefuroxime showed changes in the quantity and distribution of polysaccharides in the capsular layer and that treatment made it easier for complement C3 to bind to the bacterial surface. In this study, the presence or absence of the complement C3 bound to the surface of K. pneumoniae treated with sub-MIC cefodizime and the CL re sponse of human polymorphonuclear leuko cytes were investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Encapsulated Klebsiella pneumo niae has been shown to be resistant to phago cytosis in the absence of specific anticapsular antibodies because the bacterial surface has a negative net charge and is mostly hydrophilic [6,7], Previously, we reported that the treat ment of K. pneumoniae with a sub-MIC of cefodizimc reduced the thickness of the cap sular layer and that these changes increased the surface hydrophobicity of the bacteria and decreased the negative charge of the bacterial surface to render K. pneumoniae more sus ceptible to phagocytic activity by reducing the physical repulsion between the bacteria and phagocytes [8], Most encapsulated bacteria are not opsonized by complement because the capsular polysaccharides prevent comple ment binding and subsequent opsonophagocytosis [9][10][11]. Williams [ 12] showed that sub-MIC of cefuroxime altered the quantity and distribution of capsular polysaccharides of K. pneumoniae, making it easier for comple ment C3 to bind to the bacterial surface.…”
Section: Introductionmentioning
confidence: 98%